KEDUDUKAN PERATURAN OJK DALAM MENGATUR PEMEGANG SAHAM PENGENDALI BPR DAN BPRS - Kurniawan, I Gede Hartadi; Judge, Zulfikar; Muliawan, Anatomi (Lex Jurnalica, 2025)
AbstractBank Perekonomian Rakyat is a type of Bank needed by Micro and Small and Medium Enterprises for business development for small and medium communities. Bank Perekonomian Rakyat is located throughout the Republic of Indonesia with private ownership or under the local government, which in private ownership, of course follows the provisions for establishing a Limited Liability Company in carrying out business activities, both in establishing a business, arranging management, mergers or consolidations to closing the business entity. A Limited Liability Company business entity has an absolute decision from the General Meeting of Shareholders in determining anything in carrying out company activities including in terms of consolidation or mergers, especially for the Bank Perekonomian Rakyat and Bank Perekonomian Syariah industries, which also mostly have the status of a Limited Liability Company Legal Entity. The issuance of Financial Services Authority Regulation number 7 of 2024 concerning Bank Perekonomian Rakyat and Bank Perekonomian Syariah also regulates the consolidation or merger of Bank Perekonomian Rakyat including forced consolidation relating to the provisions for ownership of controlling shareholders who have the status of controlling shareholders in more than 1 Bank Perekonomian Rakyat and are required to consolidate the Bank Perekonomian Rakyat Business Entity from 2 or more Business Entities to one Business Entity. This is not in accordance with Law Number 40 of 2007 concerning Limited Liability Companies which stipulates that decisions on consolidation or merger of Business Entities are the authority of the General Meeting of Shareholders. Keywords: consolidation, Bank Perekonomian Rakyat, Limited Liability Companies AbstrakBank Perekonomian Rakyat adalah jenis Bank yang dibutuhkan oleh Usaha Mikro dan Kecil Menengah untuk pengembangan usaha bagi masyarakat kecil dan menengah. Bank Perekonomian Rakyat berlokasi di seluruh penjuru Negara Kesatuan Republik Indonesia dengan kepemilikan swasta atau dibawah pemerintah daerah , yang pada kepemilikan swasta, tentunya mengikuti ketentuan pendirian Perseroan Terbatas dalam menjalankan kegiatan usaha, baik dalam pendirian usaha, pengaturan kepengurusan, merger atau konsolidasi hingga penutupan badan usaha. Sebuah badan usaha Perseroan Terbatas mempunyai keputusan mutlak dari Rapat Umum Pemegang Saham dalam menentukan hal apapun dalam menjalankan kegiatan perusahaan termasuk dalam hal konsolidasi atau merger khususnya bagi industri Bank Perekonomian Rakyat dan Bank Perekonomian Rakyat Syariah yang juga mayoritas mempunyai status Badan Hukum Perseroan Terbatas. Terbitnya Peraturan Otoritas Jasa Keuangan nomor 7 tahun 2024 tentang Bank Perekonomian Rakyat dan Bank Perekonomian Rakyat Syariah juga mengatur tentang konsolidasi atau merger Bank Perekonomian Rakyat termasuk tentang konsolidasi paksa berkaitan dengan ketentuan kepemilikan pemegang saham pengendali yang mempunyai status pemegeng saham pengendali di lebih dari 1 Bank Perekonomian Rakyat dan diwajibkan untuk mengkonsolidasikan Badan Usaha Bank Perekonomian Rakyat dari 2 atau lebih Badan Usaha ke satu Badan Usaha . Hal tersebut tidak sesuai dengan Undang Undang nomor 40 .tahun 2007 tentang Perseroan Terbatas yang mengatur bahwa keputusan konsolidasi atau merger Badan Usaha merupakan kewenangan Rapat Umum Pemegang Saham Kata kunci : konsolidasi , Bank Perekonomian Rakyat, Perseroan Terbatas